Lessons from lockdown: Virtual Clinics and service reorganisation in fracture management during COVID 19 experience of an Irish Regional Trauma Unit. Issue 6 (December 2021) - Stanley, Ciaran; Kelly, Martin; Elzaki, Mohamed; Butler, Audrey; Condon, Finbarr; Lenehan, Brian
Abstract: Background: Trauma places a burden on healthcare services accounting for a large proportion of Emergency Department presentations. COVID-19 spread rapidly affecting over 30 million worldwide. To manage trauma presentations the Department of Trauma & Orthopaedic Surgery reorganised service delivery. Aim: To assess the impact of service reorganisation and Virtual Clinics on patients in a Regional Unit in Ireland. Methods: A retrospective review of trauma activity following introduction of Virtual Fracture Clinics and Theatre COVID Pathways for a 10 week period in comparison with the same 2019 period. All patients underwent both nasopharyngeal and oropharyngeal swabs PCR testing prior to operations. Theatre and outpatient activity were evaluated. Clinic data were accumulated using the Integrated Patient Management System. Results: Theatre Activity: 242 patients underwent surgery in our trauma unit (mean 2.98 per list) during the COVID- 19 period. 29 cases were performed in repurposed elective hospital giving a total of 271 during the 2020 study period. 371 cases were performed in the same 2019 period (mean 4.58 per list). Outpatient Activity: We noted a 25.86% fracture clinic referral reduction during the COVID 19 period compared to 2019. There was a 150.77% increase in patients managed through Trauma Assessment Clinic. 639 patients were managed through the Virtual Fracture Clinic Pathway during COVID 19 period. Conclusions: Over one in four fracture clinic patients can be managed virtually. A new dedicated Acute Fracture Unit within our institution permitted streamlining of care and social distancing. The "Non-COVID" pathway for ambulatory trauma was essential in managing the growing presentations of these injuries. Highlights: COVID precautions resulted in a reduction in the number of trauma theatres cases Numbers of clinic referrals also dropped significantly There is a growing role for virtual fracture clinics in the current pandemic Over 1 in 4 traditional fracture clinics can be dealt with virtually Pragmatic approaches are necessary to deal with trauma in the face of new normal